Internações pediátricas por condições sensíveis à atenção primária em hospital de referência terciária no Maranhão - Lima, Raquel Castro Desterro e Silva Moreira (2014)
Access and effectiveness of Primary Health Care are decisive to avoid hospitalizations. Therefore, Ambulatory Care Sensitive Conditions (ACSC) is an excellent indicator to evaluate Primary Health Care. In view of the relevance of this indicator to propose strategies of organization and consolidation of Sistema Único de Saúde, this study has the main purpose to analyze pediatric hospitalizations by ACSC in a tertiary referral hospital in Maranhão. It was made a descriptive and retrospective study of the epidemiological data and diagnostics collected in University Hospital of Federal University of Maranhão. The data were transferred to a database, using the IBM SPSS Statistics 20 software (2011) to do statistical analysis. The crossing of diagnostics register systems and age groups was analyzed by non parametric test of independence; when it was not possible to use test, it was used the exact Fisher test or the G independence test. To analyze frequencies of hospitalizations by ACSC among age groups within each register system was applied test of adherence. The crossings of hospitalized patients by ACSC, within each register system, and the presence or not of Unidade Básica de Saúde da Família (UBSF) near their residence, were analyzed by test of adherence, and the comparison between the register systems about the presence or not of UBSF, by the test of independence. The level of significance in all tests was 5%. The diagnostics were classified according to Brazilian List of ACSC. There were 17% of hospitalizations by ACSC. The predominant age group was 1 to 4 years old (36%), male (51,2%) and brown-skinned (60,5%). The patients came from São Luís (50%) and from interior of Maranhão (50%), and the majority was from the urban zone (65,1%) and did not have UBSF near your residence (57%). Within the ACSC groups of the Brazilian List, the most frequent was pneumonias bacterianas (25,5%), followed by the group of infecção no rim e trato urinário (19,7%). Considering the classification of ACSC Brazilian List, almost one fifth of admissions in this high complexity reference hospital in the state could have had, plausibly, resolution in Primary Health Care.